2021
DOI: 10.1186/s12931-021-01879-6
|View full text |Cite
|
Sign up to set email alerts
|

Progressive fibrosing interstitial lung disease: prevalence and clinical outcome

Abstract: Background The progressive fibrosing (PF) phenotype of interstitial lung disease (ILD) is characterised by worsening respiratory symptoms, lung function, and extent of fibrosis on high-resolution computed tomography. We aimed to investigate the prevalence and clinical outcomes of PF-ILD in a real-world cohort and assess the prognostic significance of the PF-ILD diagnostic criteria. Methods Clinical data of patients with fibrosing ILD other than idi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 34 publications
8
38
0
Order By: Relevance
“…33 Other real-world retrospective studies also reported the prevalence and clinical significance of a progressive phenotype. [34][35][36][37] Our data showed a prevalence of FILD with a progressive phenotype consistent with that predicted by a questionnaire survey, 38 and showed that patients with non-IPF FILD and clinically progressive disease have a poor prognosis. Moreover, we show that patients with non-IPF FILD and a progressive phenotype have a prognosis similar to those with IPF.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…33 Other real-world retrospective studies also reported the prevalence and clinical significance of a progressive phenotype. [34][35][36][37] Our data showed a prevalence of FILD with a progressive phenotype consistent with that predicted by a questionnaire survey, 38 and showed that patients with non-IPF FILD and clinically progressive disease have a poor prognosis. Moreover, we show that patients with non-IPF FILD and a progressive phenotype have a prognosis similar to those with IPF.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, in a recent study including 168 non‐IPF patients who had a progressive phenotype without antifibrotic agents in a real‐world setting, relative FVC decline of ≥10% in 24 months was a poor prognostic factor in patients with non‐IPF FILD 33 . Other real‐world retrospective studies also reported the prevalence and clinical significance of a progressive phenotype 34–37 . Our data showed a prevalence of FILD with a progressive phenotype consistent with that predicted by a questionnaire survey, 38 and showed that patients with non‐IPF FILD and clinically progressive disease have a poor prognosis.…”
Section: Discussionsupporting
confidence: 82%
“…In an IPF cluster analysis, progressive patients were divided into three different clusters based on three unique expression patterns of proteins, which were pondered to refer different progressive profiles [ 17 ]. In addition, among patients with non-IPF ILDs the survival was shorter in patients with disease progression than in patients with a stable disease course [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large-scale survey estimated that 18.0%-32.0% of patients diagnosed with non-IPF ILDs developed progressive fibrosis with overall survival of 61-80 months in the US, France, Germany, Italy, Spain, the United Kingdom, and Japan (Wijsenbeek et al, 2019). PF-ILD was identified in 135 of 396 (34.1%) patients with non-IPF ILDs in a cohort of Korean patients (Kwon et al, 2021). In another Chinese single-center cohort of 608 patients, 132 patients (21.7%) with ILD met the criteria for PF-ILD (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%